IMPLANTACIÓN DE LA CONTABILIDAD EN LA LICORERA “LA PANTERA” DE LA CIUDAD DE LOJA, PERIODO 01 DE ENERO AL 30 DE JUNIO DEL 2020 - Ríos Carrión, Mónica del Cisne (2021)
The present thesis work entitled IMPLANTATION OF ACCOUNTING IN THE LIQUOR COMPANY "LA PANTERA" OF THE CITY OF LOJA, PERIOD JANUARY 01 TO JUNE 30, 2020 was established in order to develop the implementation of accounting according to the needs of the liquor store that favors the performance of its activities in an efficient and quality way, which is justified, since it shows an accounting theory-practice application, through concepts, definitions and categories of commercial accounting; which has allowed the compilation, registration and interpretation of the daily commercial activities carried out by La Licorera "La Pantera" of the City of Loja, in order to obtain results that contribute to its Owner to improve the company economically. On the other hand and in accordance with the objectives that were set for the development of this work, in the Liquor Store "La Pantera" of the City of Loja, the proposal of a model for the registration of an entire accounting process is left, such as: order and filing of documents, initial and final inventories, plan; accounts manual which are used to record in the journal with their respective types of entries, which will even help to know the dates for the tax return; General ledger, trial balance, worksheet that will be of great help and finally prepare the financial statements to know the economic situation that the liquor store is going through, which will also serve as a guide in the development of its commercial and financial operations. Once the thesis work has concluded, it is determined that the implementation of accounting in the liquor store is of vital importance, therefore it provides accounting processes and techniques that allow to have clear orderly information on activities, which helps to organize and control its resources with in order to achieve greater economic benefits but in this case the results were negative with a loss of $ 10854.33 which means that the liquor store does not have sufficient liquidity, it has a high percentage of indebtedness and, most notably, at the moment it does not have a good profitability.